Gellan Gum/Alginate Microparticles as Drug Delivery Vehicles - Carrêlo, Henrique (2023)
Funding Information: This work is funded by National Funds through the FCT-Fundação para a Ciência e a Tecnologia, I.P., under the scope of the projects UID/50025/2020-2023 and LA/0037/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication-i3N. P.S. acknowledges the individual contract CEECIND.03189.2020. Publisher Copyright: © 2023 by the authors.